2009
DOI: 10.1038/jid.2008.310
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-Associated Macrophage-Induced Invasion and Angiogenesis of Human Basal Cell Carcinoma Cells by Cyclooxygenase-2 Induction

Abstract: Tumor-associated macrophages (TAMs) and cyclooxygenase-2 (COX-2) are associated with invasion, angiogenesis, and poor prognosis in many human cancers. However, the role of TAMs in human basal cell carcinoma (BCC) remains elusive. We found that the number of TAMs infiltrating the tumor is correlated with the depth of invasion, microvessel density, and COX-2 expression in human BCC cells. TAMs also aggregate near COX-2 expressing BCC tumor nests. We hypothesize that TAMs might activate COX-2 in BCC cells and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
281
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(301 citation statements)
references
References 26 publications
14
281
2
4
Order By: Relevance
“…NECA, specific adenosine receptor agonists, and antagonists were used to characterize the effect of adenosine receptor modulation on NR4A1-3 receptor expression in monocytic cell types used in numerous similar studies including primary human PBMCs, THP-1, and murine raw macrophage 264.7 cells (24)(25)(26)(27)(28). PMA was further used to differentiate THP-1 monocytes to an alternative macrophage phenotype (PMA-differentiated THP-1 cells) (29).…”
Section: Resultsmentioning
confidence: 99%
“…NECA, specific adenosine receptor agonists, and antagonists were used to characterize the effect of adenosine receptor modulation on NR4A1-3 receptor expression in monocytic cell types used in numerous similar studies including primary human PBMCs, THP-1, and murine raw macrophage 264.7 cells (24)(25)(26)(27)(28). PMA was further used to differentiate THP-1 monocytes to an alternative macrophage phenotype (PMA-differentiated THP-1 cells) (29).…”
Section: Resultsmentioning
confidence: 99%
“…Researches have demonstrated that PMA-induced macrophages and M2-polarized macrophages shared the same profile (Tjiu et al, 2009). The phenotype and function of M2-polarized macrophages were very similar to that of TAM (tumor-associated macrophages), but M2-polarized macrophages were still not equaled to TAM (Grivennikov et al, 2010(Grivennikov et al, , 2010Mantovani et al).…”
Section: Il-12 Treatment Increased B7-h1 Expression In Ovarian Cancermentioning
confidence: 99%
“…15 Macrophage polarization was achieved by treating the cultured monocyte-derived macrophages with 20 ng/mL IFN-g and 100 ng/mL of LPS (to induce M1 phenotype), 20 ng/mL IL-4 (to induce M2 phenotype), or no cytokines (subsequently referred to as M0), for 2 d. Relative gene expression was calculated by the 2 ¡DDCT method as previously described. 16 Data were calculated as the fold change in expression of the target gene relative to housekeeping gene (GAPDH).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%